2018
DOI: 10.1007/s00270-018-1919-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Measures After Sclerotherapy of Venous Malformations: A Systematic Review

Abstract: The published literature over the past 10 years shows no clear method to evaluate the effect of sclerotherapy for venous malformation. We suggest that a standard set of outcome measures should be defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…There is no clear method to evaluate the outcomes of sclerotherapy for VM. 17 Several publications report there is a discrepancy between radiologic and clinical outcomes after VM sclerotherapy. 7,[11][12][13]18 Bianchini, G et al reported significant improvement in the symptoms in intramuscular VMs with sclerotherapy even when 83.9% of the posttreatment MRI showed no significant change of the VMs.…”
Section: Discussionmentioning
confidence: 99%
“…There is no clear method to evaluate the outcomes of sclerotherapy for VM. 17 Several publications report there is a discrepancy between radiologic and clinical outcomes after VM sclerotherapy. 7,[11][12][13]18 Bianchini, G et al reported significant improvement in the symptoms in intramuscular VMs with sclerotherapy even when 83.9% of the posttreatment MRI showed no significant change of the VMs.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of outcome measurements for vascular malformations is limited by the quality of available literature, with wide range of excellent (8%-95%), good (11%-90%), and poor (5%-16%) results. 23 De Maria et al 24…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of outcome measurements for vascular malformations is limited by the quality of available literature, with wide range of excellent (8%–95%), good (11%–90%), and poor (5%–16%) results 23 . De Maria et al 24 published a systematic review of sclerotherapy agents used for VMs of the face, head, and neck.…”
Section: Discussionmentioning
confidence: 99%
“…stated that the past literature shows no clear method to evaluate the effect of sclerotherapy. 12 They also expressed that future studies should be related to anatomic location and depth of the malformation. In this study we compared the treatment results of extra- and intramuscular VM’s after Polidocanol sclerotherapy with the patient’s subjective evaluation of the outcome and QOL after the treatment.…”
Section: Discussionmentioning
confidence: 99%